The Role of Adjuvant Radiotherapy for a Case of Primary Breast Sarcoma: A Plan Comparison between Three Modern Techniques and a Review of the Literature - Mariella Cozzolino; Caterina Oliviero; Barbara D’Andrea; Giuseppe Guglielmi; Giorgia Califano; Rocchina Caivano; Antonella Bianculli; Vincenzo Fusco (Case Reports in Medicine)
A 65-year-old woman, affected by a malignant fibrous histiocytoma (undifferentiated pleomorphic sarcoma) of the left breast, presented to our department to receive the postoperative radiotherapy. In the absence of prospective and randomized trials and investigations on breast sarcoma irradiation in literature, due to the rarity of this pathology, the role of adjuvant radiotherapy remains unclear. To identify the best radiotherapy technique for this patient, three methods were compared: 3D conformal radiotherapy (3D-CRT), intensity-modulated radiation therapy (IMRT), and volumetric arc therapy (VMAT) or RapidArc® (RA). 50 Gy was prescribed to the chest wall and 66 Gy to the tumor bed. Three plans were designed, and target coverage, organs-at-risk sparing, and treatment efficiency were compared. IMRT and RA improved both target coverage and dose uniformity/homogeneity. Planning objective for the lung is always satisfied comparing the different techniques, but the volume receiving 20 Gy drops to 17% by RA compared to 3D-CRT. The heart volume receiving 30 Gy was 10% by IMRT, against 13% and 16% by RA and 3D-CRT. The monitor unit (MU) required by 3D-CRT was 527 MU, followed by RA and IMRT. Treatment time was similar with 3D-CRT and RA but doubled using IMRT. Although all three radiotherapy techniques offered a satisfactory solution, RA and IMRT offer some improvement on target coverage, dose homogeneity, and conformity for this particular case of breast sarcoma.